ANALISIS KEWENANGAN PENJABAT KEPALA DESA DALAM MEMIMPIN SEBUAH DESA PEMEKARAN (Studi Kasus Desa Sepantak Kecamatan Belitang Hilir Kabupaten Sekadau) - NIM. A1011211122, MELLA APRIASTUTI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Sepantak Village is an expansion village of Sungai Ayak Dua Village in the Belitang Hilir Sub-district of Sekadau Regency. The expansion of Sepantak Village aims to increase the effectiveness of services to the community, accelerate regional development, and provide space for community participation in a village government that is more independent and responsive to local needs. Sepantak Village is currently led by an Acting Village Head because at the time of its formation, no Village Head elections had been held. An official is someone who holds an official position in an organization, institution, or government, with certain authorities and responsibilities regulated by regulations or laws. This research is used to determine: 1) How is the Authority of the Acting Village Head in Leading a Village Expansion? 2) What are the Factors that Obstruct the Acting Village Head in Leading a Village Expansion? This research uses a qualitative approach with the type of field research. Data collection techniques using observation and interviews. Data analysis techniques using purposive sampling. The conclusions of this research are: 1) The Acting Village Head has full authority like the Definitive Village Head to run the government, carry out development, and empower the community in the expansion village. 2) What are the factors that hinder the acting village head in leading a village expansion? This research is a study using a qualitative approach with the type of field research (Field Research). Data collection techniques using observation and interviews. Data analysis techniques using purposive sampling. The conclusions of this research are: 1) The Acting Village Head has full authority like the Definitive Village Head to run the government, carry out development, and empower the community in the expansion village. 2) The challenges faced include administrative arrangements, limited human resources, funding, and infrastructure. 3) In exercising its authority, the Acting Village Head always tries to involve the community in the decision-making process through the village deliberation forum. Keywords: Village Expansion, Acting Village Head, Acting Village Head. Abstrak Desa Sepantak merupakan sebuah desa pemekaran dari Desa Sungai Ayak Dua di Kecamatan Belitang Hilir Kabupaten Sekadau. Pemekaran Desa Sepantak bertujuan untuk meningkatkan efektivitas pelayanan kepada masyarakat, mempercepat pembangunan daerah, serta memberikan ruang bagi partisipasi masyarakat dalam pemerintahan desa yang lebih mandiri dan responsif terhadap kebutuhan lokal. Desa Sepantak saat ini dipimpin oleh seorang Penjabat Kepala Desa karena pada saat pembentukannya, belum ada pemilihan Kepala Desa (Pilkades) yang diselenggarakan. Pejabat adalah seseorang yang memegang suatu jabatan atau posisi resmi dalam sebuah organisasi, lembaga, atau pemerintahan, dengan kewenangan dan tanggung jawab tertentu yang diatur oleh peraturan atau undang-undang. Penelitian ini digunakan untuk mengetahui : 1) Bagaimana Kewenangan Penjabat Kepala Desa Dalam Memimpin Sebuah Desa Pemekaran? 2) Apa Faktor-Faktor Yang Menghambat Penjabat Kepala Desa Dalam Memimpin Sebuah Desa Pemekaran?. Penelitian ini adalah penelitian dengan menggunakan pendekatan kualitatif dengan jenis penelitian lapangan (Field Research). Teknik pengumpulan data menggunakan observasi dan wawancara. Teknik analisis data menggunakan purposive sampling. Hasil Kesimpulan penelitian ini yaitu: 1) Penjabat Kepala Desa memiliki kewenangan penuh seperti halnya Kepala Desa Definitif untuk menjalankan pemerintahan, melaksanakan pembangunan, dan memberdayakan masyarakat di desa pemekaran. 2) Tantangan yang dihadapi mencakup penataan administrasi, keterbatasan sumber daya manusia, pendanaan, serta infrastruktur. 3) Dalam menjalankan kewenangannya, Penjabat Kepala Desa selalu berupaya melibatkan masyarakat dalam proses pengambilan keputusan melalui forum musyawarah desa. Kata Kunci: Desa Pemekaran, Penjabat Kepala Desa, Penjabat